Queer gothic – queer modernism - Sobolczyk, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The article discusses the motifs of queerness (homosexuality) in classical (English) Gothic novels and indicates a parallel with the modern practices of reading and writing queerness. Additionally, it defines the place of queer Gothic on the map of queer Modernism at the turn of the 19th century and in the 20th century. Simultaneously, he poses a question about the reason for pushing this aesthetics to the margins of that whichis “highly artistic”, or its presence only in the mainstream – basically through pastiche, grotesque, stylization or the sole use of formal elements in a polyphonic or Silva rerum structure.